Amanajé: ferramenta de suporte a comunicação interna nas organizações de desenvolvimento de software - Ian Alex Serrão Belém (Brasil, 2019)
Nowadays, technology is gaining more and more space in the business environment, regardless of whether it is a company, the implementation of management software has become very important to save time, activities that are used with accurate information and especially , agility in conducting a given project. In this context, no software project management is no different, as there must be ways to enable communication so that participants exchange information accurately and do not tire of the focus of the project. With this, you can manage exchanged communications, always ensuring certain information and making available the items involved in the project at the exact time they are needed. When in-house communication does not occur, those involved in the project are exposed to failures and risks that may delay software delivery, reduce budget and decrease the quality of services provided. In this scenario, this paper aims to develop a tool to support internal communication in software development activities. The methodology was based on a quantitative research to identify as the main tools used in development companies and in the development of tools and perception of communication between project teams. Therefore, obtained as a result of an Internal Communication Tool called Amanajé, which means messenger in Tupi-Guarani. An evaluation of the tool included nineteen participants from eight software development companies in Manaus-AM. The results of this evaluation show very promising, which shows that the proposed tool can contribute to a very positive form of communication of a software project team.